Ag-doped FeSe0.94 polycrystalline samples obtained through hot isostatic pressing with improved grain connectivity. (21st July 2016) - Gajda, G; Morawski, A; Rogacki, K; Cetner, T; Zaleski, A J; Buchkov, K; Nazarova, E; Balchev, N; Hossain, M S A; Diduszko, R; Gruszka, K; Przysłupski, P; et al.
Abstract: We evaluate the effects of high pressure during annealing on the structural and superconducting properties of Ag-doped FeSe bulks. The results obtained in this work indicate that the annealing at high pressure increases the critical temperature, upper critical field and irreversibility field due to the improved uniformity and grain connectivity.